HUBUNGAN ASUPAN PROTEIN, FE, ZINC, ASAM FOLAT, VITAMIN B12, KONSUMSI ZAT INHIBITOR DENGAN KEJADIAN ANEMIA GIZI BESI PADA MAHASISWI PRODI GIZI UPNVJ - Naila Antania Hanjani (2022)
Anemia is one of the nutritional problems in Indonesia, and most commonly found in the group of women of childbearing age. College students are included in the category of Women of Childbearing Age with an age range of 18-28 years. Factors that can affect anemia are intake of protein, iron, zinc, folic acid, vitamin B12, dan consumption of inhibitors (tannins, phytates, oxalates, dan caffeine). The purpose of this study was to determine the relationship between consumption of protein, iron, zinc, folic acid, vitamin b12, and consumption of inhibitor substances with the incidence of iron nutritional anemia in undergraduate nutrition study program students of UPNVJ. This study used a cross sectional study design. The sampling method used a Stratified Random Sampling technique. The subjects in this study were 65 female students. Hemoglobin levels were taken offline using Easy Touch GCHB, and data on intake of protein, iron, zinc, folic acid, vitamin B12, dan inhibitors were obtained through offline interviews using SQ-FFQ. The results of bivariate analysis using chi-square showed a relationship between protein intake dan anemia (p= 0.000), iron intake dan anemia (p= 0.000), zinc intake dan anemia (p= 0.000), folic acid intake dan anemia (p= 0.000), intake of vitamin B12 with anemia (p= 0.000), and consumption of inhibitors with anemia (p= 0.001). This shows that there is a relationship between the consumption of protein, iron, zinc, folic acid, vitamin b12, dan consumption of inhibitor substances with the incidence of iron nutritional anemia in undergraduate nutrition study students of the UPNVJ.